Teacher's beliefs about the use of technologies by families to get involved in education - Militza Lourdes Urías Martínez; Maricela Urías Murrieta; Ángel Alberto Valdés Cuervo (Universidad de Guadalajara, 2017)
The present qualitative study aimed to understand teacher's beliefs about the benefits of the use of Information and Communication Technologies (ICT) by the families of the students, and of the educational practices to encourage the use of ICT by parents. Interviews were conducted with 12 teachers from urban public elementary schools, eight women and four men, aged between 23 and 55 years. The information was analyzed with the inductive method. It was found that teachers consider that ICT use by families improves support for home learning, cultural capital of students, and communication with parents. Teachers believe that they encourage families to use ICT when they handle it to inform them about homework and school activities. It was concluded that the teachers consider that the management of ICT by the families favors the teaching process. However, their beliefs about practices that promote their use by families are limited. These findings suggest that while teachers are aware of the benefits of ICT, it is necessary to train them to favor a wider use of technologies by families.